A Model for Internalizing Prophetic Leadership Values in Islamic Religious Education Learning through ‘Morning Religious Sermons (Kultum Pagi)’ Activities in Schools - Muhamad Umar Hasibullah; Ivatu Sofia (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This study aims to describe the model of internalizing prophetic leadership values in Islamic Religious Education learning through the “Morning Kultum” activity at SMA Al-Furqon Jember. The research is grounded in the school’s need to develop students who are not only academically competent but also possess Islamic character and leadership skills relevant to contemporary challenges. Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The findings indicate that the morning kultum serves as an effective medium for internalizing prophetic leadership values including trustworthiness, exemplary conduct, moral courage, discipline, and character building by engaging students directly in preparing, delivering, and reflecting on kultum material. Teachers act as facilitators who provide guidance, direction, and motivational support, enabling the internalization process to occur naturally and continuously. This activity enhances students’ communication skills, confidence, religious character, and visionary mindset aligned with the principles of rahmatan lil ‘alamin. The study recommends the development of varied themes, methods, and evaluation mechanisms to strengthen the morning kultum as a sustainable and adaptive model for Islamic character formation in schools.